Management of Unexpected Expenditures for Covid-19 in Local Government - Basri, Yesi Mutia; Hariadi, Hariadi; Asra, Ode (Jurnal Ilmiah Akuntansi dan Bisnis, 2021)
This study aims to explore how the Riau Provincial Government manages unexpected expenses in the face of the Covid-19 pandemic. The method in this study is a qualitative method with the type of case study. Data collection techniques used are interviews, observation, and documentation. The results showed that the management of unexpected costs was carried out through the planning stage by reallocating and centralizing the budget. At the administrative and accountability stage, there are problems in recording Unexpected Expenditures, namely the absence of clear technical guidelines regarding the implementation of Unexpected Expenditures, setting spending limits for emergencies. There is no valid data for the distribution of aid funds for MSMEs affected by Covid-19 as well as valid documents for recording third party grant assistance. This research contributes to the government in making policies in financial management in disaster emergencies. Keywords : Covid-19 pandemic, financial management, refocusing, reallocation, administration